STUDENTS’ PERCEPTION TOWARD WATTPAD AS MEDIA TO ENHANCE READING SKILL - Wahyuni, Sri; syatriana, Eny; mallapiang, Yassir (FKIP Unismuh Makassar, 2024)
The objective of this research was to find out the students’ perception toward wattpad as media to enhance reading skill at fourth semester in English Education Department Universitas Muhammadiyah Makassar. The researcher used descriptive quantitative research. The sample of this research was D Class of English education department students Universitas Muhammadiyah Makassar which consist of 10 students. The Data was taken by using questioner with Google form .The data from questionnaire shows that mostly students considered the wattpad application to be a helpful for enhancing students' reading kills. It means reading in wattpad has a good impact on English learning activities in fourth semester students of the English Deparment of Muhammadiyah Makassar.